Rancang Bangun Sistem Pendukung Keputusan Penentuan Kelayakan Pinjaman Nasabah (Studi Kasus Koperasi Ridho Rizki) - Sakti, Alfian Wira Satya; Sutomo, Erwin; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Ridho Rizki Employees Cooperative a credit union that aims to provide storage services and lending capital to the surrounding community Karangmojo village. Areas of the business process scope Employees Cooperative Ridho Rizki is, cash loans, savings, compulsory savings and voluntary savings. In the process of lending cash, a cooperative judge of eligibility or the total penalty payment history, amount of loan, collateral value, and the value of their business, then if deemed appropriate by the owner of the loan will be realized. However, problems that occur in the cooperative over the years is the presence of the owners are not there so that the loan application is in the cooperative accumulate and can not be realized by the owner. Besides the problem that also occurred in the cooperative is the assessment of any owner in realizing loans are subjective, resulting in some customers in arrears installment payments already overdue. Resolve the issue then be made an eligibility determination decision support system that is able to replace the loan customers of the assessment process owners and provide a precise calculation in assessing the feasibility of loan customers. Methods which can support the decision are Fuzzy logic, because the data and installment payments on the cooperative nature of non-linear so that it can be modeled and calculated exactly.